Innovating Physics Education with the Archio Application to Enhance Interest in Learning Archimedes' Law - Saqila, Maya Shinta; Pramudita, Finna; Hakim, Marsa Raihanida; Saputra, Riski Yulianto; Hudaa, Syihaabul; Suryadi, Ahmad (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2024)
The main problem in physics education among students is the lack of interest in learning due to monotonous teaching methods such as lectures. Lectures are often considered uninteresting and ineffective. This research aims to assess the effectiveness of a Thunkable-based application named Archio in increasing learning interest. The study uses the 4-D development model (Define, Design, Develop, Disseminate) and was conducted at the end of 2023. The Define stage involved a survey to identify students' learning difficulties, which showed Archimedes' Law as the most difficult material. The Archio application was then designed (Design) and developed (Develop) with features such as learning materials, interactive simulations, quizzes, and reflections. At the Disseminate stage, the application was introduced through posters. The application received scores of 4.30 and 4.20 from expert and student validation results. The validation results indicated that the application is suitable for use with a very good category. The recommendation from this research is further development of the Archio application based on validator feedback to ensure its wider and smoother usage